2015
DOI: 10.4085/1062-6050-51.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Vibration While Squatting and Delayed-Onset Muscle Soreness in Women

Abstract: Context: Research into alleviating muscle pain and symptoms in individuals after delayed-onset muscle soreness (DOMS) has been inconsistent and unsuccessful in demonstrating a useful recovery modality.Objective: To investigate the effects of short-term wholebody vibration (WBV) on DOMS over a 72-hour period after a high-intensity exercise protocol.Design: Randomized controlled clinical trial. Setting: University laboratory.Patients or Other Participants: Thirty women volunteered to participate in 4 testing ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Additionally, the pressure pain threshold (PPT) is frequently used as an index for rating the intensity of muscle pain, 49 but differences in the units used to measure PPT in the current literature meant that it could not be used in the current analysis. For example, PPT was recorded in N, 8 Kpa, 15 or kg/cm, 40 and varied in numerical values at different ranges and locations. [41][42][43] Furthermore, the range of motion was explored in different joints, including the knee in two studies 15,36 and the elbow in one.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the pressure pain threshold (PPT) is frequently used as an index for rating the intensity of muscle pain, 49 but differences in the units used to measure PPT in the current literature meant that it could not be used in the current analysis. For example, PPT was recorded in N, 8 Kpa, 15 or kg/cm, 40 and varied in numerical values at different ranges and locations. [41][42][43] Furthermore, the range of motion was explored in different joints, including the knee in two studies 15,36 and the elbow in one.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Furthermore, some studies only presented the mean and standard deviation in figures, and no further information was obtained by attempted correspondence with the authors. 5,15,16,[26][27][28][29][30][31] Five studies did not include information on VAS (primary outcome) or CK (secondary outcome), 2,[31][32][33][34] and only one trial demonstrated the magnitudes of changes in VAS and CK. 17 One abstract was deemed to be too low quality, with confusion between the groups and a lack of units for CK levels.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…During the split squat, the back leg was placed on a padded bench for support and the knee was placed into 90° of flexion, allowing focus on single leg performance of the front leg. We provided assistance on the concentric phase after the participants reached 90° of knee flexion of the front knee on the exercising leg, allowing greater focus on the eccentric phase [ 26 , 27 ]. Immediately following EIMD protocol, participants were re-assessed for balance and torque measurements.…”
Section: Methodsmentioning
confidence: 99%
“…First, (whole body-) vibration therapy, which is often been considered as potentially enhancing neuromuscular performance in athletes has been described in several studies to show beneficial effects in alleviating symptoms of DOMS [63]. Otherwise, Dabbs et al concluded in a randomized controlled trail with 30 healthy, recreationally trained women, that exposure to whole-body vibration did not effectively manage DOMS after high-intensity exercise [64]. Second, therapeutic ultrasound (TU) is controversially discussed.…”
Section: Physical Therapy and Acupuncturementioning
confidence: 99%